Articulating “Archiannelids”: Phylogenomics and Annelid Relationships, with Emphasis on Meiofaunal Taxa - Andrade, Sónia C.S.; Novo Rodríguez, Marta; Kawauchi, Gisele Y.; Worsaae, Katrine; Pleijel, Fredrik; Giribet, Gonzalo; Rouse, Greg W. (Molecular Biology and Evolution, 2015)
This research was supported by the Bivalve Assembling the Tree-of-Life project (http://www.bivatol.org, last accessed July 25, 2015), by the US National Science Foundation (NSF) AToL program (grants DEB-0732854/0732903/0732860), and by NSF DEB-0844596 and 0844881: Collaborative Research: Resolving Old Questions in Mollusc Phylogenetics with New EST Data and Developing General Phylogenomic Tools. In addition, it has been supported by internal funds from the Museum of Comparative Zoology and from Scripps Institution of Oceanography. The authors thank the Carlsberg Foundation (Grant no. 2009_01_0053) for an expedition to Greenland and Gordon and Betty Moore Foundation (Moorea Biocode Project) for an expedition to French Polynesia. Annelid disparity has resulted in morphological-based classifications that disagree with phylogenies based on Sanger sequencing and phylogenomic analyses. However, the data used for the latter studies came from various sources and technologies, involved poorly occupied matrices and lacked key lineages. Here, we generated a new Illumina-based data set to address annelid relationships from a fresh perspective, independent from previously generated data and with nearly fully occupied matrices. Our sampling reflects the span of annelid diversity, including two symbiotic annelid groups (Myzostomida and Spinther) and five meiofaunal groups once referred to as part of Archiannelida (three from Protodrilida, plus Dinophilus and Polygordius). As well as the placement of these unusual annelids, we sought to address the overall phylogeny of Annelida, and provide a new perspective for naming of major clades. Our results largely corroborate the phylogenomic results of Weigert et al. (2014; Illuminating the base of the annelid tree using transcriptomics. Mol Biol Evol. 31:1391-1401), with “Magelona + Owenia” and Chaetopteridae forming a grade with respect to all other annelids. Echiura and Sipuncula are supported as being annelid groups, with Sipuncula closest to amphinomids as sister group to ...